RATIONAL COST OF DIARRHEA TREATMENT IS LOWER THAN THE IRRATIONAL - Harun R, Cholik; Liawati, Eulis (Jurnal Keperawatan, 2012)
This research was conducted to analyze the way how to find out a diarrheal treatment in Ponorogo regency and to estimate the economical cost of the irrational diareal treatment. This was an observational research that used cross sectional design. The number of respondent of the research was 100 children with diarrheal disease. To analyze the different between diarrheal cost treatment, the resesearcher used a statistical test of independent t-test with level of significance p < 0,05. The finding of diarrheal treatment behaviour revealed that most of it was catagorized irrational (60%) which effected the higher cost of treatment.